From trash to resource: recovered-Pd from spent three-way catalysts as a precursor of an effective photo-catalyst for H2 production. Issue 9 (26th January 2016) - Gombac, V.; Montini, T.; Falqui, A.; Loche, D.; Prato, M.; Genovese, A.; Mercuri, M. L.; Serpe, A.; Fornasiero, P.; Deplano, P.
Abstract : The synthesis and catalytic activity of a new effective catalyst for methanol and glycerol photo-reforming prepared using the valued product of a sustainable Pd-leaching from spent TWCs, are described. Abstract : The successful production of a nanostructured and highly dispersed Pd-TiO2 photo-catalyst, using [Pd(Me2 dazdt)2 ](I3 )2 (Me2 dazdt = N, N ′-dimethyl-perhydrodiazepine-2, 3-dithione) salt, obtained through the selective and safe recovery of palladium from model exhaust three-way catalysts (TWCs), is reported here. The photo-catalyst prepared by the impregnation/photo-reduction of palladium on the support showed improved performance in H2 production from methanol and in glycerol photo-reforming compared to reference photo-catalysts obtained from conventional Pd-salts. The reported results represent a case of successful palladium "recovery and re-employment" and thus constitute an example of green chemistry by providing, in one route, the environmentally friendly recovery of a critical metal and its employment in the renewable energy field.